The most important skin diseases of the sheep and the goat - GIADINIS (Ν. Δ. ΓΙΑΔΙΝΗΣ) N. D.; SARIDOMICHELAKIS (Μ.Ν. ΣΑΡΙΔΟΜΙΧΕΛΑΚΗΣ) M. N. (Journal of the Hellenic Veterinary Medical Society, 2018)
Skin diseases of small ruminants may have an economical impact, apart from the fact that some of them can be transmitted to humans. In this review article, the most important environmental, nutritional, parasitic, bacterial, fungal, viral, immune-mediated and neoplastic skin diseases of the goat and sheep are presented, emphasising on the clinical features, the diagnosis and the treatment.